Corynoneura Winnertz and Thienemanniella Kieffer from the Nearctic Region (Diptera: Chironomidae: Orthocladiinae) - Fu, Yue; Sæther, Ole A. (Zootaxa, 2012)
Twenty-one Nearctic species of Corynoneura Winnertz and Thienemanniella Kieffer are reviewed. Nine new species aredescribed and illustrated; C. acuminata sp. n., C. ascensa sp. n., C. caudicula sp. n., C. disinflata sp. n., C. floridaensissp. n. and C. macula sp. n. as male, female, pupa and larva; C. hortonensis sp. n. and C. porrecta sp. n. as male andfemale; and C. capitanea sp. n. as pharate male. Eight species, C. collaris Makarchenko et Makarchenko C. doriceniMakarchenko et Makarchenko, C. edwardsi Brundin, C. lobata Edwards, C. scutellata Winnertz, Thienemanniellalobapodema Hestenes et Sæther, T. tiunovae Makarchenko et Makarchenko, and T. xena (Roback) are reexamined basedon Nearctic specimens. Additionally, C. fittkaui Schlee is mentioned, and four species with males unknown are included.Keys to all stages of the Nearctic Corynoneura are presented, and keys to Thienemanniella are updated. The lateral lamel-lae on the coxosternapodeme and the shape of labia of adult females are shown to be excellent distinguishing features for species in Corynoneura.